ENTEROSORBENT APPLICATION IN THE COMPLEX THERAPY OF MONO AND MIXED VARIANTS OF THE ROTAVIRAL INFECTION AMONG CHILDREN - Yu.B. Belan; N.A. Polyanskaya (Union of pediatricians of Russia, 2008)
The given article highlights an important aspect of the acute enteric infections among the infants - application of the enterosorbents. Noteworthy to say that the latter takes part not only in the egestion of the endo and exotoxins from the human organism but also in the elimination of a causative agent. The authors convincingly showed an advantage of medications from this group in the treatment, as they drastically reduced the relief terms for the disease symptoms and patients recovery.Key words: acute enteric infections, rotaviral infection, treatment, enterosorbents, children.